2012
DOI: 10.1007/s10531-012-0225-2
|View full text |Cite
|
Sign up to set email alerts
|

Sand pits as habitats for beetles (Coleoptera): does area affect species number and composition?

Abstract: Species living in open sandy habitats are declining in northern Europe because of habitat loss and degradation. However, mining of sand creates potential new habitats for these species in the form of sand pits. In this study we investigated the beetle fauna in sand pits in order to determine what kind of sand pits are the most valuable for conservation, in terms of sand pit area (primarily) and the proportion of sand material, vegetation cover, tree cover and edge habitats. Thirteen sand pits in Uppsala County… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The most attractive to bees were the wastelands resulting from extractive industry. Also, earlier studies showed that sand pits or gravel pits are important habitats readily colonized by various insect species, including rare ones, with specific environmental or food requirements (Lönnberg and Jonsell 2012;Heneberg et al 2013). Quarries belong to specific environments in the landscape with bare soil patches maintained by regular human disturbances and occupied mainly by synanthropic vegetation.…”
Section: Attractiveness Of Wastelandsmentioning
confidence: 99%
“…The most attractive to bees were the wastelands resulting from extractive industry. Also, earlier studies showed that sand pits or gravel pits are important habitats readily colonized by various insect species, including rare ones, with specific environmental or food requirements (Lönnberg and Jonsell 2012;Heneberg et al 2013). Quarries belong to specific environments in the landscape with bare soil patches maintained by regular human disturbances and occupied mainly by synanthropic vegetation.…”
Section: Attractiveness Of Wastelandsmentioning
confidence: 99%
“…We argue that, beyond vegetation, soil texture must also be considered in order to allow local animal communities to establish in restored areas. This opportunity should also be taken to promote and preserve valuable open sand habitats on quarrying sites (Lönnberg & Jonsell ).…”
Section: Discussionmentioning
confidence: 99%
“…Apalus bimaculatus inhabits open sandy areas (Lönnell and Edelsjö 2004), a habitat that has declined in Northern Europe following changes in land use where a reduction in grazing and forest fires has promoted re-vegetation of these areas (Emanuelsson 2009). Unless active vegetation removal is carried out, this habitat usually becomes over-grown and unsuitable for sand-living beetles within a decade (Lönnell and Edelsjö 2004; Lönnberg and Jonsell 2012). Thus, the habitat specialisation of A. bimaculatus has resulted in this species having a highly fragmented distribution in central and southwest Sweden (Cederberg 2003, Lönnell and Edelsjö 2004; Lönnell 2005).…”
Section: Introductionmentioning
confidence: 99%